Tanggapan Masyarakat terhadap Legenda Genuk Kemiri dan Sendang Sani: Eksistensi Cerita Rakyat dalam Masyarakat (Sebuah Kajian Resepsi Sastra) - Tya Resta Fitriana; Sita Nuraseh; Exwan Andriyan Verrysaputro (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2024)
This research aims to determine the existence of these folk tales and the challenges faced to maintain their existence. This research uses a synchronous method. This is done to see the response of literary readers in one era. This research data consists of words and information from sources and documents related to folklore in the Pati Regency. The document used is a book entitled Pati Folk Tales: For Children and the General Public by Sri Widyaati, S.Pd., M.Pd. CV Arindri Hijrah published this book. Data in the form of words from informants comes from interviews with elders and guards of the Genuk Kemiri and Sendang Sani sites. The sampling technique is a proportional sampling; community respondents are taken according to the age range according to the Ministry of Health, which is divided into nine age ranges. The results of this research show that the distribution of Sendang Sani and Genuk Kemiri folklore is fading day by day because as the years go by, they tend not to know about these folk tales, but people are still willing to preserve these folk tales because of the many values ​​contained in them.